Expression of LncRNA-BCYRN1 in pediatric asthma and related factors of disease induction - Huang, Xufeng; Huang, Zhengguo; Shao, Chengliang; Zheng, Bin; Zhang, Jing (Cellular and Molecular Biology, 2022)
The study aimed to investigate the expression of lncRNA-BCYRN1 in serum of pediatric asthma patients and the related factors of disease induction. For this purpose, a total of 95 patients were randomly selected from the outpatient department of pediatrics of a hospital affiliated with the medical university from October 2018 to October 2019, including 25 intermittent episodes, 25 mild persistent episodes, 20 moderate persistent episodes, and 20 severe persistent episodes. In addition, serum samples from 30 healthy control children were selected for comparison. The expression levels of lncRNA-BCYRN1 and the inflammatory factors IL-4, IL-12, IL-37, 25-(OH)D in serum were detected by real-time quantitative fluorescence PCR(qrt-PCR), and the influence of the expression of lncRNA-BCYRN1 on the prognosis of children and its correlation with the expression of TNF-a and IgE were analyzed. Results: the expression of LncRNA BCYRN1 was positively correlated with the expression of TNF-α and IgE (r=0.712, 0.748, all P<0.001). Serum IL-4 levels in each group were 21.06±2.93pg/ml, 23.88±3.91pg/ ml, 25.85±4.02pg/ml, and 17.74±1.77pg/ml, respectively. Serum IL-4 levels in each group were higher than those in the normal control group, and the difference was statistically significant (P<0.001). The levels of IL-12, IL-37 and 25-(OH)D in all the affected groups were decreased compared with the normal control group, while the serum levels of IL-37 were negatively correlated with IL-4 and positively correlated with IL-12 and 25-(OH)D. Conclusion: serum IL-4 level of children in the disease group was increased, indicating hyperexpression of Th2 cell function, and serum IL-12 and IL-37 levels were decreased, suggesting decreased Th1 cell function, indicating Th1/Th2 imbalance in children with asthma. The low serum vitamin D level of children in the disease group was negatively correlated with serum IL-4 level and positively correlated with IL-12 and IL-37 levels, which may be the trigger factor of inflammation in asthmatic diseases and should be supplemented in clinical treatment. The expression level of lncRNA-BCYRN1 is related to the severity of pediatric asthma, which can be used as a prognostic indicator and has a certain effect on the prognosis of clinical pediatric asthma.